THE ROLE OF CONTEXT AND DISCOURSE IN ENHANCING LANGUAGE LEARNING EFFICIENCY (Лучшие интеллектуальные исследования, 2025)
Abstract: The significance of foreign language proficiency has escalated in recent years, especially with globalization and the need for cross-cultural communication. Among the factors influencing language acquisition, context and discourse are paramount. This article explores their essential role in improving language learning, especially in developing speaking abilities. It examines theoretical concepts of context and discourse, their contribution to speaking skills, and offers practical teaching recommendations for integrating these elements into English language instruction.